MODERATION OF ISLAMIC CORPORATE GOVERNANCE ON CORPORATE SOCIAL REPORTING DISCLOSURES - Saragih, Fitriani; Nainggolan, Edisah Putra (Proceeding International Seminar of Islamic Studies, 2024)
Disclosure Information about impact social, environmental, and economic from the operation business, will give transparency to various holder interests about How the company manages the impact on society and the environment. Information disclosed can influence the perception and reputation company in the eyeholder's interest. Study This aims To disclose related matters with Corporate social reporting policy in the Sharia banking industry in Medan City. The Corporate social reporting policy will be tested by using Islamic Corporate Governance as a moderating variable with the perception of society and image positive as variables that influence it. Population study This is customers Sharia banking in Medan City is Bank Muamalat Indonesia and Bank Syariah Indonesia with a sample of as many as 100 people. Research results show that Positive Perception Image is influential Regarding CSR. Perception positively about CSR can increase the reputation company in the eyes of consumers, customers and stakeholders interest other. ICG is influential towards CSR, The influence of Islamic Corporate Governance (ICG) on Corporate Social Responsibility (CSR) reflects How Islamic values and principles influence the policies and practices of a company is not quite enough to answer social. Research results show Perception and image are positively moderated by ICG. ICG can ensure that Sharia principles are accommodated with Good in Company policies and practices.